UPAYA PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI METODE GLOBAL PADA SISWA KELAS 2 SD NO 112/VI RANTAU KERMAS KECAMATAN JANGKAT - Supitma Arnita; Aulia Susanti; Randi Eka Putra; Yahfenel Evi Fussalam (Jurnal Tunas Pendidikan, 2025)
This study aims to improve the beginning reading skills of grade II students of SD Negeri No. 112/VI Rantau Kermas, Jangkat District, by applying the global method. The global method is used because it provides a learning approach that starts from the introduction of sentences as a whole before students learn words and letters separately. The subjects of this study were students of elementary school class NO 112/VI Rantau Kermas, Jangkat District, 2024/2025 school year with a total of 15 students, consisting of 5 male students and 10 female students. This class action research was carried out in two cycles, where each cycle consisted of two meetings. The research instruments used include observation sheets of educator activities, observation sheets of student learning activities, and learning outcomes tests at the end of each cycle. The results showed a significant improvement in students' beginning reading skills from Cycle I to Cycle II. In Cycle I, the average student learning completeness reached 60.87%, while in Cycle II it increased to 82.61%. In addition, the observation results showed an increase in student learning activities as well as educators' performance in implementing learning with the global method. The percentage of students in the “Very Good” category increased from 26.09% in Cycle I to 52.17% in Cycle II, with no students in the “Poor” category at the end of the study.